Participatory Ecofeminism for the Preservation of the Religio-Ecological Identity of Indigenous Communities - Indra Jaya, Ramlan (Fakultas Dakwah UIN KHAS Jember, 2025)
The preservation of the religio-ecological identity of indigenous communities is threatened by deforestation and the marginalization of local knowledge. In Sumatra, 2.5 million hectares of forest were lost (2001–2021), including areas inhabited by the Orang Rimba, who have lost access to sacred sites. Top-down policies like REDD+ (Reducing Emissions from Deforestation and Forest Degradation) frequently fail due to the exclusion of indigenous women’s participation and spiritual values, while prior research has fragmented gender, ecological, and participatory aspects without holistic integration. This study aims to develop a participatory ecofeminism model that strengthens religio-ecological identity through collaboration among indigenous communities, activists, and policymakers, with a focus on participation mechanisms, the impact of deforestation on indigenous rituals, and the integration of spiritual values into advocacy. The research method employed a qualitative approach, including Focus Group Discussions (FGDs) with 150 Orang Rimba participants, ethnography, and surveys, to explore traditional practices, women’s roles, and socio-ecological dynamics in Riau. Findings revealed that indigenous women’s participation in environmental management (e.g., Tana’ Ulen in Kalimantan) reduced environmental degradation by 40%. The integration of spirituality and ecology through rituals such as Seren Taun functioned as ecological early warning systems. Trans-local solidarity networks (e.g., the Indigenous Women’s Network for Biodiversity) strengthened advocacy rooted in local wisdom. The study uncovered contradictions between global policies (SDGs/REDD+) that neglect spiritual dimensions and the need for community-based inclusive approaches. Recommendations include integrating local wisdom into educational curricula and advancing policy reforms through participatory governance